HUBUNGAN FUNGSI SEKSUAL TERHADAP KUALITAS HIDUP PADA WANITA USIA 17-35 TAHUN DI INDONESIA - Fadel Khatami (Nusantara Hasana Journal, 2021)
Fulfilled sexual needs can have several positive impacts on individuals such as physical health, physical well-being in general (Azhar, Basyir, and Alfitri 2016). The quality of life of Indonesia's population is low, Indonesia ranks 108 out of 177 countries (Widianti 2007). of this study was to examine sexual relations on the quality of life of women of reproductive age in Indonesia. The design used is descriptive. This design is used to see the relationship between sexual function and quality of life in Indonesia in 2020. The results of the research conducted by researchers based on the chi square show that there is no relationship between sexual function and the quality of life of women aged 17-35 in Indonesia in 2020 because the results of the chi-square test show that p-value = 0.159> 0.05 food is provided. there is no relationship between sexual function and quality of life in women in Indonesia. means a person cannot be defined with certainty, only that person can define it, because the quality of life is something that is subjective. It is suggested that in further research to use other methods of interviewing data, such as interviews.